2016
DOI: 10.1590/0103-5150.029.001.ao15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of back pain among high school students in a municipality in southern Brazil

Abstract: Prevalence of back pain among high school students in a municipality in southern Brazil [I] Prevalência de dor nas costas em escolares do ensino médio em uma cidade no sul do Brasil [A] Cíntia Detsch Fonseca [a] , Cláudia Tarragô Candotti [a] , Matias Noll [a] , Anna Maria Hecker Luz [b] , Antônio Cardoso dos Santos [a] , Carlos Otávio Corso [a] * [a] Universidade Federal do Rio Grande do Sul, (UFRGS), Porto Alegre, RS, Brazil [b] Universidade Vale do Rio dos Sinos, (UNISINOS), Porto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
5
10
0
4
Order By: Relevance
“…This result was in agreement with [35,45] who did not find an association between back pain and mode of transport of school supplies. Also, another study conducted among school children aged from 11 to 16 years by [14] they found no significant association between type of school bag carrying school materials and back pain.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result was in agreement with [35,45] who did not find an association between back pain and mode of transport of school supplies. Also, another study conducted among school children aged from 11 to 16 years by [14] they found no significant association between type of school bag carrying school materials and back pain.…”
Section: Discussionsupporting
confidence: 93%
“…This result was in accordance with study conducted in southern Brazil among school students by [35] they showed that more than half of students affected by pain reported moderate pain, more than one third mild pain and only 5.9% had severe pain. On the contrary, a study by [6] showed that mild pain was prevailing which reported by 44.7% of all children and youth aged 10-19 and nearly every fourth subject reported having experienced strong pain.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…When an individual remains seated for an extensive time period, he/ she tends to adopt an inappropriate posture, relaxed and curved, leading to inappropriate postural habits and causing a series of postural compensations and complaints of discomfort and pain. There is an association between inappropriate postural habits and musculoskeletal disorders in teenagers [7] and many factors can corroborate with these body modifications such as the adjustments and adaptations to their own body changes, psychosocial demands [8], questions related to the excessive weight of school backpacks and their use in an asymmetric and inappropriate way [7,9], and ergonomic difficulties [10,11].…”
Section: Introductionmentioning
confidence: 99%